Research on Defrosting System of Air-source Heat Pump with Liquid Storage Gas-liquid Separator - Ma Longxia; Liu Zixuan; Wang Fenghao; Wang Zhihua; Lou Yechun (Zhileng xuebao)
The surface of an outdoor evaporator can easily frost when an air-source heat pump is used for heating during winter. The most common defrosting method, reverse cycle defrosting, has safety risk and long defrosting period. To improve the performance of an air-source heat pump system with reverse-cycle defrosting, a defrosting system consisting of an air-source heat pump coupled with a liquid storage gas-liquid separator is proposed in this paper. Compared with traditional air-source heat pump systems, this system can effectively delay frosting and shorten defrosting period. In this study, the thermodynamic performances of an air-source heat pump system and a traditional air-source heat pump system under six working conditions were studied experimentally. The experimental results show that the system can effectively delay frosting and shorten the defrosting period in a heating-defrosting-recovery cycle; the maximum defrosting time can be delayed by 53 min, and the maximum defrosting period can be shortened by 75 s.